Association between psychological factors and temporomandibular disorders in adolescents of rural and urban zones - Claudia Restrepo; Ana Maria Ortiz; Ana Carolina Henao; Ruben Manrique (BMC, 2021)
Abstract Background Temporomandibular disorders (TMD) are related to psychological factors. Adolescence is one of the stages in life with more psychosocial vulnerability, which is dissimilar in rural and urban zones. Thus, the aim of this investigation was to evaluate the association between psychological factors (symptoms of anxiety, depression and somatization) and TMD in adolescents between 12 and 15 years, belonging to urban and rural zones of Colombia. Methods 180 subjects aged 12-15 years (mean 13.8, SD 1.2), enrolled in public schools in the rural (n = 90) and urban (n = 90) zones were included. All subjects were evaluated using the DC/TMD instrument; the Axis I was applied for the clinical examination and the Axis II for the psychological evaluation. Data were analyzed by means of T-student, Mann-Whitney, Kruskall-Wallis tests, Pearson Chi square and multiple-variable analysis with logistic regression. Results Forty percent of the included subjects presented some type of TMD. TMD related to pain were the most common (25.5% of the studied adolescents), being myalgia the most common (20% of the adolescents in urban zone and 31.1% of the adolescents in the rural zone). There was no difference between the TMD present in males and females, but there were differences in the symptoms of Anxiety, and Somatization (p < 0.05). TMD and psychological factors were more prevalent in children with 13 years of age. A statistically significant association between TMD and symptoms of Anxiety (Pearson Chi squared 25.57, p = 0.04), depression (Pearson Chi squared 33.28, p = 0.03) and somatization (Pearson Chi squared 25.79, p = 0.04) was found in subjects from rural zones. No associations between psychological aspects and TMD were found in subjects from urban zones, but overall all psychological factors significantly influenced TMD. Conclusion This study indicates Myalgia to be the most prevalent TMD in studied Colombian adolescents. Pain-related TMDs are associated with psychological factors in the adolescent population of rural Colombia. Symptoms of anxiety, depression and somatization were found to be associated to TMD, even when the frequency was not necessarily severe.